Resveratrol relieves chlorothalonil-induced apoptosis and necroptosis through miR-15a/Bcl2-A20 axis in fish kidney cells. Issue 107 (December 2020) - Li, Xiaojing; Yao, Yujie; Wang, Shengchen; Xu, Shiwen
Abstract: Chlorothalonil (CT) is a commonly used fungicide and its excessive application seriously threatens aquatic life and human health. Resveratrol (RSV) is a natural polyphenol and can be used as a therapeutic and preventive agent for the treatment of various diseases. To explore the toxic mechanism of CT exposure on fish kidney cell, as well as the alleviation effect of RSV, we established CT poisoning and/or RSV treatment fish kidney cell models. Ctenopharyngodon idellus kidney (CIK) cell line was treated with CT (5 μg/L) and/or RSV (10 μM) for 48 h. The results showed that CT exposure activated cytochromeP450s (CYPs) including CYP1A1, CYP1B1 and CYP1C, caused malondialdehyde (MDA) accumulation, inhibited glutathione (GSH) levels and glutathione peroxidase (GPX) activities, increased the expression of miR-15a and downregulated BCL2 and TNFα-induced protein 3 (TNFAIP3, A20), triggered mitochondrial pathway mediated apoptosis and receptor interacting serine/threonine kinase (RIP)-dependent necroptosis in CIK cells. However, cell death under CT exposure could be relieved by RSV treatment through inhibiting the expression of CYP1 family genes and restoring miR-15a/BCL2-A20 axis disorders. Overall, we conclude that RSV could relieve CT-induced apoptosis and necroptosis through miR-15a/Bcl2-A20 axis in CIK cells. These results enrich the toxicological mechanisms of the CT and confirm that RSV can be used as a potential antidote for CT poisoning. Graphical abstract: Image 1 Highlights: Resveratrol relieved cell death caused by chlorothalonil exposure. Resveratrol inhibited CYPs expression and oxidative stress under chlorothalonil. Resveratrol alleviated apoptosis and necroptosis by restoring miR-15a/BCL2-A20.